Haiti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper reviews key trends in Haiti's fiscal performance over the past decade and discusses various options for strengthening the fiscal system. It suggests that a key challenge will be to generate adequate resources to support development, which requires an increase in outlays on social programs, security, and infrastructure investment to at least the levels observed in other low-income countries. The paper reviews revenue trends and key features of the tax system. It also illustrates that Haiti's public sector employment is far smaller than in other countries.